European mobility in times of crisis the new context of european south-north migration - Glorius, Birgit 1970-; Domínguez Mujica, Josefina (Culture and social practice, 2017)
The global economic and financial crisis had severe impact on southern European economies and stimulated growing numbers of mainly young migrants heading north, nurturing the fear of brain drain back home. This volume compiles recent research results on European south-north migration, addressing migration processes and practices, the management of migratory moves by institutional frameworks and relevant public discourse. It thereby delivers an important contribution to the understanding of the durability and contextuality of recent European south-north migration and their consequences for European economies, politics and societies